Permasalahan Yang Dihadapi Mahasiswa Pendidikan Ekonomi Selama Mengikuti Praktik Pengalaman Lapangan (PPL) Tahun 2018 - Hidayati, Syafaatul (Universitas Hamzanwadi, 2018)
The Field Experience Practice Program (PPL) is a mandatory program for every prospective teacher student. As is the case with the eighth semester S1 students of the Economic Education Study Program at the University of Pamulang, they are required to take part in this program. This activity aims to provide a real experience for someone in carrying out their obligations related to the learning process. This PPL is also expected to be a transition process where a prospective teacher becomes a teacher. When it comes time to practice teaching experience, each prospective student will face various problems and difficulties. The purpose of this study is to find out the problems faced by Economics Education students while participating in Field Experience Practices (PPL). This study uses a Qualitative Research approach. Time The subjects of this study were 10th semester students of economics education study program as many as 10 students. Based on the results of research on the problems faced by prospective teacher students during the Field Experience Practice (PPL), it can be concluded that the problems include: (1) personal; (2) teaching preparation; (3) class participation; (4) classroom management; (5) teaching; (6) evaluation; (7) emotions; and (8) adjustment.Keywords: Problems, Students of Economic Education, motivation, Field Experience Practices (PPL)